Энергия и человек: сборник трудов Международной молодежной научной школы, 28-29 октября 2011 г., г. Томск - Кузнецов Г. В. Гений Владимирович; Максимов В. И. Вячеслав Иванович; Захаревич А. В. Аркадий Владимирович; Нагорнова Т. А. Татьяна Александровна (Томск, Изд-во ТПУ, 2011)
Заглавие с экрана